Die structure analysis of stress distribution during High-Strength Steel stamping process and experimental validation. (11th March 2010) - Zhang, G.B.; Chen, J.; Tang, Y.C.; Chen, L.; Wang, A.; Xiao, H.; Shi, L.; Jiang, H.M.
High-Strength Steel (HSS) is being widely used in automotive industry. However, load condition on die structure for HSS stamping increases sharply. A method for die-structure FEA analysis was proposed in this paper. The interaction force between forming blank and die faces was mapped onto die faces to serve as load boundary conditions for die structure analysis. A hyperbolic-bottomed-cup-drawing die was analysed and validated by experiment under several forming conditions. Results show that the predicted Von Mises stress values at specified positions coincides with the experimental ones as well within 15% error.